Generation mean analysis of gluten strength in bread wheat (Triticum aestivum): An effective utilization of micro-sedimentation test in early generation progenies - SARKAR, SUTAPA; SINGH, ANJU M; AHLAWAT, ARVIND K; CHAKRABORTI, MRIDUL; SINGH, SANTOSH K; SINGH, G P (The Indian Journal of Agricultural Sciences, 2014)
Better bread-making quality is one of the most important targets in the quality improvement programmes of wheat (Triticum aestivum L.). Gluten strength is a major indicator of bread making quality and is measured by various methods such as the SDS-sedimentation test. However, the nature of gene action for gluten strength has not been studied so far. In the present study, generation mean analysis was undertaken to estimate the nature and magnitude of gene effects for gluten strength in two sets of crosses involving contrasting parents using a less known microsedimentation test. Scaling test indicated the involvement of epistasis on the expression of the trait and inadequacy of additive-dominance model. Therefore, both six and five parameter models were used to understand the nature and direction of gene action further. Similar types of gene-action for gluten strength were recorded, albeit with some differences in the direction and magnitude of the effects, in the two sets of crosses. Among the different epistatic components, dominance × dominance effect had the maximum contribution and was acting in the negative direction in both the crosses. Analysis of both the cross combinations using Castle-Wright’ equation for ’number of effective genes/blocks’ revealed that at least one major gene block besides several minor genes could be involved for the micro-sedimentation volume.